Impact of facilities on academic performance of students with special needs in mainstreamed public schools in Southwestern Nigeria. Issue 2 (19th April 2012) - Oluremi, FAREO Dorcas; Olubukola, OJO Olakunbi
Abstract : Facilities have a great impact on academic performances of students, and inadequate facilities translate to poor performance. The study examined the availability and convenience of the facilities that were provided to students with special educational needs in mainstreamed schools. It ascertained the qualifications of teachers teaching in mainstreamed public secondary schools. It determined the relationship between availability of facilities and academic performance of students with special educational needs; and also compared the academic performance of male and female students with special educational needs. The results showed that essential facilities and materials like hand railings, hearing aids, Braille, instructional materials, and lower toilets were not available, although the few that were available (typewriters, resource rooms, wheel chairs) were in poor condition. The study showed that specialist teachers were inadequate in mainstreamed public schools in Southwestern Nigeria. There was a significant relationship between availability of facilities and academic performance of students with special educational needs. However, there was no significant difference between the academic performance of male and female students with special educational needs. The study concluded that inadequate provision of facilities and materials to mainstreamed public schools would lead to poor academic performances of students with special educational needs. Finally, adequate funding of integrated schools would help to overcome the problem of provision and maintenance of special equipment and materials for the use of students with special educational needs.